Tindak Tutur Ilokusi pada Podcast Deddy Corbuzier Palestina-Gaza-Israel: Kajian Pragmatik - Putriyansyah, Syifa Aulia; Nurhadi, Jatmika (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2024)
Deddy Corbuzier's podcast that discussed the Palestine-Gaza-Israel issue had several illocutionary speech acts providing deeper information, ideas, and thoughts about topics related to Palestine-Gaza-Israel. The purpose of this research was to find out the types, functions, and influences of illocutionary speech acts in Deddy Corbuzier's podcast,. The method used in this research was descriptive qualitative by employing listening and recording techniques. The data obtained were int the forms of the transcripts from the Deddy Corbuzier podcast video on the Youtube channel aired on November 28, 2023 with a duration of 44 minutes 59 seconds. This research found a total of 102 speech acts, dominated by the assertive speech as the discourse in the video showed clear and transparent utterances without personally crossing the line with the interlocutor to avoid any conflict even though the way of delivery was firm and straightforward. This research implied that the podcast with the topic Palestine-Gaza-Israel influenced public opinion, strengthened solidarity, enriched insight into effective communication, and social media as a suggestion for representing the issue.